Oral Health Status in India- Where Do We Stand? (Global Journal of Medical Research, 2019)
Oral health is an imperative part of general health. Moreover, dental diseases are easily preventable to a huge extent. In India, dental diseases, particularly caries and periodontal disease as well as oral cancer, still continues to be widespread in the population. Only two large scale Oral Health Surveys were conducted in the country till now: (i) National Oral Health Survey & Fluoride Mapping by Dental Council of India in 2003 and (ii) Oral Health in India: Report of multi-centric oral health survey by Ministry of Health and Family Welfare in collaboration with Dental Department AIIMS in 2005. This article highlights the desperate necessity of a nationwide oral health survey for proper identification and correction of real barriers in achieving good oral health for the population.
Keywords: oral health status; national health survey; india